Deviant and criminal behavior in the workplace - Elias, Steven M. (Psychology and crime series., 2012)
Workplace crimes are never far from the news. From major scandals like Enron to violent crimes committed by co-workers to petty theft of office supplies, deviant and criminal behavior is common in the workplace. Psychological factors are almost always involved when an employee engages in such behavior. Deviant and Criminal Behavior in the Workplace offers insights at the level of the individual employee and also sheds light on the role organizations themselves may play in fostering such criminal behavior. The volume considers psychological factors involved in theft and fraud, workplace violence, employee discrimination, and sexual harassment.